2016
DOI: 10.3348/kjr.2016.17.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted MRI of Malignant versus Benign Portal Vein Thrombosis

Abstract: ObjectiveTo validate the diffusion-weighted MRI (DWI) for differentiation of benign from malignant portal vein thrombosis.Materials and MethodsThe Institutional Review Board approved this retrospective study and waived informed consent. A total of 59 consecutive patients (52 men and 7 women, aged 40–85 years) with grossly defined portal vein thrombus (PVT) on hepatic MRI were retrospectively analyzed. Among them, liver cirrhosis was found in 45 patients, and hepatocellular carcinoma in 47 patients. DWI was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
1
17
1
4
Order By: Relevance
“…In this study and in a few of literature studies, no statistically significant differences were demonstrated between different b values with malignant and benign PVT ADC values due to reasons mentioned above (25). Beside this, particularly in malignant thrombotic tissues, high signal intensities are observed in DW-MRI, due to high cell density and secondary to prevented diffusion.…”
Section: Dw-mri Was First Used In Cranial Imaging In the Diagnosiscontrasting
confidence: 60%
“…In this study and in a few of literature studies, no statistically significant differences were demonstrated between different b values with malignant and benign PVT ADC values due to reasons mentioned above (25). Beside this, particularly in malignant thrombotic tissues, high signal intensities are observed in DW-MRI, due to high cell density and secondary to prevented diffusion.…”
Section: Dw-mri Was First Used In Cranial Imaging In the Diagnosiscontrasting
confidence: 60%
“…Besides, published studies have reported high diagnostic accuracy (up to 95%) for differentiating malignant component from benign PVT by gadoxetic acid-enhanced MR imaging [36]. Susceptibility-weighted MRI was superior to diffusionweighted MR imaging in distinguishing the malignant component in portal vein with a high diagnostic capability (AUC, 0.989; sensitivity, 95%; specificity, 95.5%) [37][38][39][40].…”
Section: Discussionmentioning
confidence: 95%
“…Improved MRI performance due to multichannel surface receiver coils, parallel imaging techniques, fat suppression schemes, DWI, adoption of the hepatocyte specific contrast agents and multiple arterial phases has improved the performance of liver MRI for lesion detection and liver function evaluation ( 20 21 22 23 24 25 26 27 ). However, as mentioned above, an enhanced MRI has some limitations and the focus of this study was on a non-contrast MRI as a potential HCC surveillance tool.…”
Section: Discussionmentioning
confidence: 99%